(untitled) (Research, Society and Development, 2021)
Tecoma stans (L.) Juss. Ex Kunth is a species belonging to the Bignoniaceae family, popularly known as yellowing, yellow bell, and garden little ipe. Studies with T. stans seeds are scarce and it have potential in the search for natural compounds with biological activities. This study aimed to evaluate the toxicity and antioxidant activity of the ether extract (EE) and fractions from T. stans seeds. The EE was obtained in Soxhlet apparatus with petroleum ether and fractions were obtained by hydrolysis and esterification reactions. Phytochemical screening evaluated the presence of steroids, triterpenoids, alkaloids, coumarins and anthraquinones in EE. The toxicity was evaluated by the A. salina lethality test and antioxidant activity by DPPH method. It was observed the presence of steroids, triterpenoids and alkaloids in EE, which had no toxicity to A. salina (LC50 > 1000 µg/mL). The fractions of seeds exhibited toxicity on A. salina. All samples showed antioxidant activity with EC50 between 0.9 and 1.1 µg/mL. These results indicated potential applications for T. stans seeds.